ANALISIS KESULITAN SISWA KELAS VIII DALAM MENYELESAIAKN SOAL POLA BILANGAN DI SMP NEGERI 1 LAHUSA - Yuliarman Zendrato (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2026)
The problem of this research is the difficulty of class VIII students in solving pola bilangan problems. The aims of this research were 1) to determine the difficulties experienced by students in solving pola bilangan at SMP Negeri 1 Lahusa and 2) to find out the factors causing students' difficulties in solving pola bilangan at SMP Negeri 1 Lahusa. The approach and type of this research is a descriptive approach and a qualitative type. The subjects in this research were class VIII students at SMP Negeri 1 Lahusa, totaling 24 students. This research instrument used data reduction, data presentation (Data Display), drawing conclusions (verification). The results of the research showed that 9 students in class concepts, 13 students had difficulty in calculations, and 15 students had difficulty understanding questions. students who have difficulty in understanding questions with a percentage of 63%. It can be concluded that the results of the research show that class VIII students at SMP Negeri 1 Lahusa in the pola bilangan material are still experience difficulty in using concepts, calculating and understanding questions. by researchers are 1) Mathematics teachers should provide more frequently training for students in completing arithmetic operations and using solving methods, especially for pola bilangan. 2) It is hoped that students will be motivated in learning mathematics and eliminate wrong assumptions about mathematics so that they can focus more on studying mathematics so that they better understand the material being taught.